Assessment of an independent solar/diesel power generation system for an inaccessible community in Algeria - Amara Mohamed; Mostefai Mohamed; Sekour Mhamed (Institute of Advanced Engineering and Science, 2022)
In general, for isolated regions, the cost of extending the electricity grid is very high. Among the solutions, we can use diesel generators (DG) and photovoltaic systems. In this work, we have studied the two Structures using the hybrid system solar-diesel with AC/AC coupling and AC/DC coupling. With the help of the HOMER program, a technical-economic analysis of the system and comparing the cost and the optimal configuration in a mountainous area isolated from the power grid is made, as well as a comparison between the cost and amount of energy produced annually corresponding to two proposed structures. The results showed that hybrid system AC/AC coupling is the suitable solution that gives technical and economic performance and environmental pollution reduction, with low cost and ecology energy compared to the energy generated by the second structure.